FACTORS AFFECTING ONLINE PURCHASE DECISION OF SPINACH VEGETABLES IN PURWOKERTO THROUGH TUKANG SAYUR SITE: FACTORS AFFECTING ONLINE PURCHASE DECISION OF SPINACH VEGETABLES IN PURWOKERTO THROUGH TUKANG SAYUR SITE - Martiana Nur Nugraheni; Tinjung Mary Prihtanti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tanjungpura, 2020)
Abstract: The research objectives was to analyze the characteristics and behavior of buying vegetable such as spinach by online, to find out the factors that influence the buying decision by online through tukangsayur.co. This research was conducted online in August, 2020 in Purwokerto areas. Determination of the sample using quota sampling with 70 respondents. The data analysis using binary logistic regression. The results showed that the respondents who made the buying decision of spinach preferred to make purchases online. Partially by age variable, income, price perception, and quality of product perception influenced significantly to decision chance of the spinach buying decision in Tukangsayur.co, while perception variable of trust has no significant effect on the spinach buying decission on Tukangsayur.co in Purwokerto areas. Keywords: spinach, online purchase, decision, logistic regression, perception